Evaluation of small extracellular vesicles isolation methods from human serum for downstream miRNA profiling - Yong, Ling Sou; Pei, Paulina Suu Tan; Nur Afrina Muhamad Hendiri; Wickneswari Ratnam; Tilakavati Karupaiah; Chilian, William M; Shamsul Mohd Zain; Sharifah Zamiah Syed Abdul Kadir; Yan, Pan; Pung, Yuh-Fen (Penerbit Universiti Kebangsaan Malaysia, 2025)
Exosomes are a type of extracellular vesicles that carry distinct profiles of biomolecules such as lipids, proteins, DNAs, and RNAs. Despite many years of research, there is still a lack of standardized methods to isolate exosomes from clinical samples for their downstream applications. Thus, this study compared three different methods, which are differential ultracentrifugation (DUC), polyethylene glycol-based precipitation (PEG), and a combination of both (PEG+UC) to isolate exosomes from human serum. The isolated exosomes were evaluated by their size distribution, recovered particle concentration, particle-to-protein ratio, exosomal marker expression, and miRNA recovery. Our results indicated that all three methods successfully isolated exosomes, however, with varying yield and purity. In particular, PEG+UC produced exosomes of both high yield and high purity, DUC produced exosomes of both low yield and low purity, whereas PEG produced exosomes of high yield but low purity. Using miR-30d-5p and let-7i-5p as selected targets, our qPCR results indicated significant differences in terms of exosomal miRNA recovery between all three methods. Overall, the PEG+UC method appeared to be a less labor-intensive alternative that can isolate exosomes of both high yield and high purity from human serum without compromising the yield of miRNAs.